Mat Kilau kebangkitan pahlawan: a cognitive study through Freytag's dramatic structure / Dona Lowii Madon ... [et al.] - Madon, Dona Lowii; Harun, Azahar; Ridzuan, Abd Rauf; Alias, Aidah; Meor Hamzah, Meor Hasmadi (Faculty of Art and Design, 2023)
The popularity of film storylines that glorify heroes fighting for their nation has spread throughout Malaysia. This advancement has increased the income of the country's creative industry while also improving the talents of creative professionals. Due to the high level of competition, special effects, shooting techniques, and even storytelling processing are the primary factors employed in enhancing a film's success. Using Freytag's Pyramid, the film Mat Kilau is a case study to identify students' knowledge of the film's narrative and camera skills and techniques. Open-ended questionnaires were delivered to 37 students in free-form written responses to obtain a wealth of information about how the respondents think and relate to what they have learnt over the semester. The content analysis measures how often certain words, subjects, and ideas appear in a text. The approach turns qualitative input into quantitative data to draw accurate conclusions about what people thought of the movie. In this study, the data suggest that students pay more attention to sequences with many sound effects, different forms of camera tracking, and rapid shot changes. The selection of students who felt the best scene served as the film's Climax is observed.